PENGARUH IKLIM KOMUNIKASI TERHADAP KINERJA KARYAWAN RUMAH SAKIT IBU DAN ANAK ERIA BUNDA PEKANBARU - Villa Pristilla; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The purpose of this study was to determine and analyze how much influence the communication climate to employee performance Mother and Child Hospital Eria Bunda Pekanbaru. The method used is descriptive research with quantitative methods. The population in this study were all employees at Women and Children's Hospital Eria Bunda Pekanbaru. Samples are drawn with a probability proportional sampling technique. The sampling method used was probability sampling with simple random sampling technique. The scale of measurement used is a Likert Scale. Data collection techniques used in this study is the observation and questionnaires. As for the analytical technique used is the descriptive statistical methods. The results showed that the relationship between communication climate (independent variable) with employee performance (the dependent variable) has a strong relationship level. Communication climate contributed considerable influence on the performance of employees at the Mother and Child Hospital Eria Bunda Pekanbaru.Keywords: communication climate, employee performance, rsia eria bunda pekanbaru